2018
DOI: 10.1186/s12889-018-6124-z
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-randomised trial on participatory community-based outdoor physical activity promotion programs in adults aged 65–75 years in Germany: protocol of the OUTDOOR ACTIVE intervention trial

Abstract: BackgroundDespite its well-known benefits for health and well-being physical activity levels are insufficient and declining with age in Germany. Physical activity promotion programs for older adults are often not successful, one reason is insufficient relevance of intervention measures for the study population. Community-based participatory research (CBPR) is a possible key strategy for tailoring more meaningful intervention programs to a specific community. However, evidence for the effectiveness of CBPR in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…The present study evaluated the effects of a multidisciplinary intervention program on AS in community dwelling old adults, with a focus on the particular role of a tailored physical exercise program on top of other ongoing actions such as nutritional counseling, cognitive stimulation, and control of comorbidities and promotion of overall wellbeing. The health benefits of exercise have been extensively documented in all age groups, mainly due to its direct benefits on muscular strength, motor skills, cardiorespiratory fitness and overall health [1]. Accordingly, our results demonstrated significant benefits of the physical exercise intervention program, mainly a significant decrease in brachial BP, particularly in the pulsatile components (SBP and PP), and an improvement in PWV, illustrating a significant BP-independent de-stiffening effect.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The present study evaluated the effects of a multidisciplinary intervention program on AS in community dwelling old adults, with a focus on the particular role of a tailored physical exercise program on top of other ongoing actions such as nutritional counseling, cognitive stimulation, and control of comorbidities and promotion of overall wellbeing. The health benefits of exercise have been extensively documented in all age groups, mainly due to its direct benefits on muscular strength, motor skills, cardiorespiratory fitness and overall health [1]. Accordingly, our results demonstrated significant benefits of the physical exercise intervention program, mainly a significant decrease in brachial BP, particularly in the pulsatile components (SBP and PP), and an improvement in PWV, illustrating a significant BP-independent de-stiffening effect.…”
Section: Discussionsupporting
confidence: 62%
“…One additional benefit of the physical activity program was the increased motivation for adopting healthy lifestyles as the person becomes physically more fit, which translated into a better nutritional profile as depicted in the MNA scores from baseline to post-intervention. Of course, these behavioral changes, if maintained, can contribute to delaying the onset of chronic diseases, supporting functional mobility and independent living, which is pivotal to promoting health, autonomy and social participation [1][2][3][4][5][6][7][8]. The functional gains are also of the utmost importance, and our results shown that tailored exercise training program produces a better body composition (positive modulation of the lean-to-fat body ratio), more strength (handgrip) and better self-efficacy for exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The OUTDOOR ACTIVE study is part of the regional prevention network AEQUIPA (Physical activity and health equity: primary prevention for healthy ageing) [16]. Research goals of OUTDOOR ACTIVE are to assess prevalence of PA in older adults, explore barriers and drivers for being physically active, and to develop and implement a community-based outdoor PA promotion program [17]. First baseline data were collected between October 2015 and August 2016 using 1) a self-administered paper-pencil questionnaire regarding intrapersonal, interpersonal, and environmental determinants of PA, 2) a short physical examination (anthropometry and blood pressure) followed by a tness test (modi ed public domain Senior Fitness Test [18] and handgrip strength test), and 3) accelerometry to objectively measure PA over the course of seven consecutive days.…”
Section: Study Design and Populationmentioning
confidence: 99%